2016
DOI: 10.1515/jbcpp-2015-0118
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of repeated administration of the first generation abused synthetic cannabinoid CP47,497

Abstract: A series of in vivo and in vitro assays were conducted to characterize the pharmacological effects of the first generation abused synthetic cannabinoid CP47,497, a racemic bicyclic cannabinoid that is similar in structure to the potent, high-efficacy synthetic cannabinoid CP55,940. CP47,497 was less efficacious than CP55,940 in activating G-proteins and dose-dependently produced common CB1 receptor-dependent pharmacological effects (i.e. catalepsy, hypothermia, antinociception, and hypolocomotion). CP47,497 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…THC produces most of its pharmacological effects through the activation of two G-protein coupled receptors, cannabinoid receptor type 1 (CB 1 ; Matsuda et al, 1990) and type 2 (CB 2 ; Munro et al, 1993). THC and other CB 1 receptor agonists effectively attenuate withdrawal signs in opioid-dependent rodents (Hine, Friedman, et al, 1975;Bhargava, 1976a,b;Vela et al, 1995;Lichtman et al, 2001;Cichewicz and Welch, 2003;Ramesh et al, 2011;Gamage et al, 2015), though this pharmacological approach elicits acute cannabimimetic side effects and results in tolerance and physical dependence after repeated administration (Wiley and Martin, 2003;Grim et al, 2016;Trexler et al, 2018Trexler et al, , 2019. Alternatively, inhibitors of monoacylglycerol lipase (MAGL; Dinh et al, 2002) and fatty acid amide hydrolase (FAAH; Cravatt et al, 1996), which hydrolyze the respective endogenous cannabinoids, 2-arachidonoylglycerol (2-AG; Mechoulam et al, 1995;Sugiura et al, 1995) and anandamide (AEA; Devane et al, 1992), attenuate naloxone-precipitated and spontaneous withdrawal signs in morphine-dependent mice with reduced cannabimimetic side effects (Ramesh et al, 2011(Ramesh et al, , 2013Gamage et al, 2015;Wills et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…THC produces most of its pharmacological effects through the activation of two G-protein coupled receptors, cannabinoid receptor type 1 (CB 1 ; Matsuda et al, 1990) and type 2 (CB 2 ; Munro et al, 1993). THC and other CB 1 receptor agonists effectively attenuate withdrawal signs in opioid-dependent rodents (Hine, Friedman, et al, 1975;Bhargava, 1976a,b;Vela et al, 1995;Lichtman et al, 2001;Cichewicz and Welch, 2003;Ramesh et al, 2011;Gamage et al, 2015), though this pharmacological approach elicits acute cannabimimetic side effects and results in tolerance and physical dependence after repeated administration (Wiley and Martin, 2003;Grim et al, 2016;Trexler et al, 2018Trexler et al, , 2019. Alternatively, inhibitors of monoacylglycerol lipase (MAGL; Dinh et al, 2002) and fatty acid amide hydrolase (FAAH; Cravatt et al, 1996), which hydrolyze the respective endogenous cannabinoids, 2-arachidonoylglycerol (2-AG; Mechoulam et al, 1995;Sugiura et al, 1995) and anandamide (AEA; Devane et al, 1992), attenuate naloxone-precipitated and spontaneous withdrawal signs in morphine-dependent mice with reduced cannabimimetic side effects (Ramesh et al, 2011(Ramesh et al, , 2013Gamage et al, 2015;Wills et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The primary contribution of the present study was the use of pA 2 /pK B analyses to determine CB 1 R heterogeneity of THC, the well characterized SCs CP55,940 and WIN55,212-2, the well characterized abused SCs JWH-073 and CP47,497, and the emerging novel abused SC A834,735D (Frost et al, 2008;Grim et al, 2016b;Marshell et al, 2014;Pertwee, 2006) in producing common in vivo cannabimimetic pharmacological effects (i.e., catalepsy, antinociception, and hypothermia) in male and female mice. These findings build on our recent study demonstrating that these drugs do not elicit relevant antinociceptive, cataleptic, and hypothermic effects in CB 1 (2/2) mice (Grim et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Studies used THC and the following five SCs reported to have higher efficacy than THC at CB 1 Rs (in order from purported highest to lowest efficacy): A-834,735 degradant (A-834,735D), WIN55,212-2 and CP55,940, JWH-073, and CP47,497 (Breivogel et al, 1998;Griffin et al, 1998;Auwärter et al, 2009;Atwood et al, 2011;Thomas and Wiley, 2014;Grim et al, 2016).The m opioid receptor agonist morphine and dopamine receptor antagonist chlorpromazine were tested as controls that were expected to produce in vivo effects independent of CB 1 R density. A-834,735D, WIN55,212-2, CP47,497, JWH-073, and chlorpromazine were obtained from Cayman Chemical (Ann Arbor, MI), and morphine, THC, and CP55,940 were generously supplied by the National Institute on Drug Abuse Drug Supply Program.…”
Section: Drugsmentioning
confidence: 99%
“…The drugs selected for study included THC, the well-characterized SCs CP55,940 and WIN55,212-2, two SCs associated with abuse CP47,497, JWH-073 (Atwood et al, 2011), and the heat degradant of the SC A-834,735 (Frost et al, 2010). Published (Griffin et al, 1998;Grim et al, 2016), and preliminary data suggest that these compounds display a range of CB 1 R efficacies as assessed in vitro by maximal stimulation of [ 35 S]GTPgS binding, such that low (e.g., THC), moderate (e.g., JWH-073, CP47,497), and high (e.g., CP55,940, WIN55,212-2, A-834,735D) degrees of CB 1 R efficacy are represented. The noncannabinoids morphine and chlorpromazine, which are active in subsets of these assays (Wiley and Martin, 2003), served as comparison drugs.…”
Section: Introductionmentioning
confidence: 99%